Optimised NSAIDs-loaded Biocompatible Nanoparticles - Roullin, V. Gaëlle; Callewaert, Maïté; Molinari, Michaël; Delavoie, Franck; Seconde, Aurélie; Andry, Marie-Christine (Nano-Micro Letters, 2010)
In this formulation study, biocompatible non steroidal anti-inflammatory (NSAIDs)-loaded nanoparticles were designed as models to be further integrated in a prosthesis surface functionalization. A modified spontaneous emulsion-solvent diffusion methodology was used to produce drug-loaded PLGA nanoparticles without any purification or solvent evaporation requirements. Formulation parameters, such as lactide/glycolide ratio, polymer concentration, solvent/non solvent ratio and non solvent phase, as well as the non ionic tensioactive P188 co-precipitation composition were systematically explored. The optimized formulation (mean size: 145 nm, surface charge: −13 mV) was employed to encapsulate various amounts of NSAIDs in a simple and scalable manner. The drug release was characterized in vitro by a complete release for 48 h. These results encourage upcoming preliminary steps for in vivo experiments of prosthesis surface functionalization.